2011
DOI: 10.1164/rccm.201103-0536oc
|View full text |Cite
|
Sign up to set email alerts
|

A Multisite Assessment of the Quantitative Capabilities of the Xpert MTB/RIF Assay

Abstract: Rationale: The Xpert MTB/RIF is an automated molecular test for Mycobacterium tuberculosis that estimates bacterial burden by measuring the threshold-cycle (Ct) of its M. tuberculosis-specific real-time polymerase chain reaction. Bacterial burden is an important biomarker for disease severity, infection control risk, and response to therapy. Objectives: Evaluate bacterial load quantitation by Xpert MTB/RIF compared with conventional quantitative methods. Methods: Xpert MTB/RIF results were compared with smear-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
95
1
9

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(120 citation statements)
references
References 26 publications
(28 reference statements)
15
95
1
9
Order By: Relevance
“…We also examined all of the Xpert assays (whether positive or negative for M. tuberculosis) for evidence of partial PCR inhibition. A sample was considered to show evidence of partial PCR inhibition when the cycle threshold (C T ) of the Xpert assay's internal control reaction was greater than 34 (24). Assays with internal control C T values of Ͼ34 were observed in 0 EBC samples, 1 (3.8%) saliva sample, 3 (12.5%) blood samples, 5 (19.2%) urine samples, 8 direct (3.3%) sputum samples, and 11 (4.2%) concentrated sputum samples (P value of inhibition in direct sputum samples versus EBC samples is 0.6, versus saliva samples is 0.1, versus blood samples is 0.07, versus urine samples is 0.001, and versus sputum pellets is 0.64).…”
Section: Patient Enrollment and Sample Accrualmentioning
confidence: 99%
See 1 more Smart Citation
“…We also examined all of the Xpert assays (whether positive or negative for M. tuberculosis) for evidence of partial PCR inhibition. A sample was considered to show evidence of partial PCR inhibition when the cycle threshold (C T ) of the Xpert assay's internal control reaction was greater than 34 (24). Assays with internal control C T values of Ͼ34 were observed in 0 EBC samples, 1 (3.8%) saliva sample, 3 (12.5%) blood samples, 5 (19.2%) urine samples, 8 direct (3.3%) sputum samples, and 11 (4.2%) concentrated sputum samples (P value of inhibition in direct sputum samples versus EBC samples is 0.6, versus saliva samples is 0.1, versus blood samples is 0.07, versus urine samples is 0.001, and versus sputum pellets is 0.64).…”
Section: Patient Enrollment and Sample Accrualmentioning
confidence: 99%
“…It has been shown that the Xpert assay is equally sensitive when performed with either type of sputum sample (19). However, the assay also provides quantitative information in the form of a cycle threshold (C T ) that has the potential to be used to monitor bacterial load (24). The quantitative information provided by these two types of sputum samples have never been rigorously compared.…”
mentioning
confidence: 99%
“…However, on its utility in pleural TB, only a few studies with small sample size have been carried out; most of these were from low-TB-burden countries (6)(7)(8), and none were from India.…”
mentioning
confidence: 99%
“…The increased variation (increased SD) in the C T values of the CDC and GLI panels (due to some Xpert MTB/RIF tests reporting delayed probe hybridization and some reporting dropout probes with no hybridization) may be attributed to the use of MGIT bulk stock, which may have increased clumping of bacterial cells compared to that of the bulk stock manufactured in the single-cell format used in the NHLS product or other factors inherent to their specific preparation. Minimal variations may, however, be more acceptable in an EQA program monitoring RIF resistance rates using differences in probe dropout or probe delayed hybridization as well as differences in C T values across the reported semiquantitative categories, since studies have already described the potential use of the Xpert assay for patient monitoring using C T values (9,15).…”
Section: Discussionmentioning
confidence: 99%
“…Resistance to rifampin (RIF) is determined by delayed or drop-out hybridization of the molecular beacon probes (5 probes span the rpoB target, and 1 probe hybridizes to the internal control). Delayed hybridization occurs when there is a Ͼ4 C T difference (for assay version G4) between any probes and dropout is reported when the C T is zero (9). The mean C T value and the SD of the C T for each probe (A to E) of each panel were calculated.…”
mentioning
confidence: 99%